Linguistic influence on mathematical development is specific rather than pervasive: revisiting the Chinese Number Advantage in Chinese and English children - Mark, Winifred; Dowker, Ann (Frontiers in Psychology, 2015)
The relative linguistic transparency of the Asian counting system has been used to explain Asian students’ relative superiority in cross-cultural comparisons of mathematics achievement. To test the validity and extent of linguistic transparency in accounting for mathematical abilities, this study tested Chinese and British primary school children. Children in Hong Kong can learn mathematics using languages with both regular (Chinese) and irregular (English) counting systems, depending on their schools’ medium of instruction. This makes it possible to compare groups with varying levels of exposure to the regular and irregular number systems within the same educational system, curriculum, and cultural environment. The study included three groups of first/second graders and third/fourth graders with varying degrees of experience to the Chinese language and counting systems: no experience (UK; n=49); spoke Chinese at home and learnt to count in English at school (HK-E; n=43); spoke Chinese at home and learnt to count in Chinese at school (HK-C; n=47). They were compared on counting, numerical abilities and place value representation. The present study also measured nonverbal reasoning, attitude towards mathematics, involvement of parents, and extra-curricular mathematics lessons to explore alternative explanations of children’s numeric ability. Results indicated that students in HK-C were better at counting backward and on the numeric skills test than those in HK-E, who were in turn better than the UK students. However, there was no statistical difference in counting forward, place value understanding, and a measure of arithmetic. Our findings add to existent literature suggesting that linguistic transparency does not have an all-pervasive influence on cross-national differences in arithmetic performance.